Barriers and enablers to accessing dental services for people experiencing homelessness: A systematic review. Issue 2 (6th January 2019) - Paisi, Martha; Kay, Elizabeth; Plessas, Anastasios; Burns, Lorna; Quinn, Cath; Brennan, Nicola; White, Sandra
Abstract: Objectives: The aim of this systematic review was to identify and conceptualize the barriers and enablers to accessing dental services for people experiencing homelessness in the United Kingdom. Methods: A literature search for studies relevant to homelessness and dental care was conducted. The PRISMA and ENTREQ guidelines were followed. Electronic databases (EMBASE, MEDLINE, DOSS, CINAHL, SOCINDEX and PsycINFO) and grey literature sources (Electronic Theses Online Service – EThOS, Kings Fund, NICE Evidence, Open Grey, Google and the Health Foundation) were searched up to 28 August 2018. The critical appraisal was conducted using CASP and an adjusted version of a JBI Critical Appraisal tool. Thematic analysis was used to develop the themes and domains. Results: Twenty‐eight papers were included. Barriers to homeless people accessing dental care stemmed both from the lived experience of homelessness and the healthcare system. Within homelessness, the themes identified included complexity, emotions and knowledge. Regarding the healthcare system, identified themes included staff encounter, accessibility and organization issues. Conclusion: Homelessness can actively contribute to both an increased need for dental care and barriers to accessing that care. The arrangement of dental healthcare services can also act as barriers to care. This is the first systematic review to conceptualize the factors associated with access to dental care for people who are homeless. It provides a set of recommendations for overcoming the main barriers for homeless people to accessing dental care. It also offers directions for future research, policy and commissioning.